2015
DOI: 10.1016/j.bbamem.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential zinc permeation and blockade of L-type Ca2+ channel isoforms Cav1.2 and Cav1.3

Abstract: Certain voltage-activated Ca2+ channels have been reported to act as potential zinc entry routes. However, it remains to be determined whether zinc can permeate individual Ca2+ channel isoforms. We expressed recombinant Ca2+ channel isoforms in Xenopus oocytes and attempted to record zinc currents from them using a two-electrode voltage clamp method. We found that, in an extracellular zinc solution, inward currents arising from zinc permeation could be recorded from Xenopus oocytes expressing L-type Cav1.2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…11, D-E). Taken together, these findings are in good agreement with previous studies showing that Zn 2+ and other d-block metal ions slow activation, often without altering channel voltage dependence, in several VGCCs lacking critical histidine residues in domain I (Magistretti et al, 2001Castelli et al, 2003;Park et al, 2015). Interestingly, most of these studies also found a less marked but significant metalinduced slowing of I Ca deactivation speed Castelli et al, 2003), an effect that was also observed in the present study (Fig.…”
Section: Micromolar Zn 2+ Concentrations Slow and Shift By Multiple Msupporting
confidence: 94%
“…11, D-E). Taken together, these findings are in good agreement with previous studies showing that Zn 2+ and other d-block metal ions slow activation, often without altering channel voltage dependence, in several VGCCs lacking critical histidine residues in domain I (Magistretti et al, 2001Castelli et al, 2003;Park et al, 2015). Interestingly, most of these studies also found a less marked but significant metalinduced slowing of I Ca deactivation speed Castelli et al, 2003), an effect that was also observed in the present study (Fig.…”
Section: Micromolar Zn 2+ Concentrations Slow and Shift By Multiple Msupporting
confidence: 94%
“…Its inhibitory effect against hyperexcitablity on calcium influx is also under investigation for other neurological diseases such as Parkinson's and multiple sclerosis (Guzman et al, 2010;Ingwersen et al, 2018). However, nimodipine is a non-selective L-type calcium channel blocker with higher potency for Ca V 1.2 than Ca V 1.3 (Park et al, 2015). Thus, its side effects on the cardiovascular system may diminish its therapeutic application (Kang et al, 2012).…”
Section: Cellular Mechanisms Underlying Llrsmentioning
confidence: 99%
“…This metal modulates negatively the heart T-type Ca 2+ channels with zinc IC 50 s of 81.7, 0.78 and 158.6 µM [ 82 ] or 196.1, 24.1 and 152.2 µM [ 83 ] for Cav3.1, Cav3.2 and Cav3.3, respectively. Regarding the N-type calcium channel, mainly expressed in neurons, zinc modulates Cav2.2 with an IC 50 of 98 µM, the P/Q-type Cav2.1 with an IC 50 of 110 µM, the R-type Cav2.3 with an IC 50 of 31.8 µM, and the L-type Ca 2+ channels (expressed mainly in smooth muscle cells) Cav1.2 with an IC 50 of 10.9 [ 83 ] or 18.4 µM; and Cav1.3 with an IC 50 of 34.1 µM [ 84 ]. In addition, intracellular zinc blocks the calcium-activated currents in the calcium-activated chloride channel (TMEM16A) with an IC 50 of 12.5 µM [ 85 ].…”
Section: Ion Channelsmentioning
confidence: 99%